2012
DOI: 10.1021/ja302329f
|View full text |Cite
|
Sign up to set email alerts
|

Construction of 1,5-Enynes by Stereospecific Pd-Catalyzed Allyl–Propargyl Cross-Couplings

Abstract: The palladium-catalyzed cross-coupling of chiral propargyl acetates and allyl boronates delivers chiral 1,5-enynes with excellent levels of chirality transfer and applied across a broad range of substrates.1,5-Enynes are important and versatile synthetic intermediates. In addition to offering differentiated π-systems for selective functionalization, 1,5-enynes can be transformed into a diverse array of cyclic structures. 1 A current challenge to reaction methodology surrounding 1,5-enynes lies in the preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 57 publications
0
27
1
Order By: Relevance
“…Subsequent 3,3′ reductive elimination affords enyne 462 with excellent es and selectivity for formation of the alkyne over the allene. 338 Consistent with this mechanism, the reaction proceeds with inversion of stereochemistry. The authors have also disclosed a related kinetic resolution, in which a chiral ligand enables the selective allylation of one enantiomer of the propargylic substrate, allowing recovery of enantioenriched starting material.…”
Section: Transition-metal-catalyzed Enantiocontrolled Allylic Substitmentioning
confidence: 81%
“…Subsequent 3,3′ reductive elimination affords enyne 462 with excellent es and selectivity for formation of the alkyne over the allene. 338 Consistent with this mechanism, the reaction proceeds with inversion of stereochemistry. The authors have also disclosed a related kinetic resolution, in which a chiral ligand enables the selective allylation of one enantiomer of the propargylic substrate, allowing recovery of enantioenriched starting material.…”
Section: Transition-metal-catalyzed Enantiocontrolled Allylic Substitmentioning
confidence: 81%
“…Less commonly, the reaction can follow an inner-sphere mechanism; in this case, the nucleophilic attack is targeted at Pd, forming an intermediate at first, followed by reductive elimination 13 14 15 16 17 18 19 20 . Recently, several studies on Pd-catalysed allylic substitution/coupling reactions via inner-sphere mechanism have been reported 21 22 23 24 25 26 27 28 29 30 31 32 33 . The key C–C bond-forming step was proposed to occur via [3,3']-reductive elimination in an allyl-Pd-allyl or allyl-Pd-nucleophile intermediate.…”
mentioning
confidence: 99%
“…Morken realized excellent regio- and enantio-selectivities in the cross-coupling of monosubstituted allyl reagents with allyl boronates under Pd catalysis ( Fig. 1b ) 28 29 30 31 32 . These results reveal the unique character of the inner-sphere mechanism; in particular, branched products can be formed as major products when monosubstituted allyl reagents are used 21 28 .…”
mentioning
confidence: 99%
“…11 Morken et al overcame this challenge by utilizing allyl boronic ester 28 as the nucleophile in the cross-coupling with propargylic acetate 27 for the synthesis of 1,5-enynes 29 (Scheme 4). 12 The success of this approach was based on the migration of the allyl group in the reductive elimination step from 31, giving rise to propargylated 29 as the major product. Although the authors focused on secondary propargylic acetates, it was shown that a quaternary all-carbon center can be introduced not only with high regioselectivity (29a), but also with complete conservation of enantiomeric enrichment (29b) when a chiral propargylic acetate was used.…”
Section: Reactivity Of Propargylic Electrophiles With Hard Nucleophilesmentioning
confidence: 99%